Assessing Impact of Metacognitive Interventions on Academic Achievement of Higher Secondary School Students in Education - Venkateswar Meher; Rajashree Baral; Sanjukta Bhuyan (Indonesian Educational Research Journal, 2024)
The present study investigates the impact of metacognitive interventions on the academic achievement of higher secondary school students in education. The study used a quasi-experimental design where two different Govt. aided higher secondary schools were selected randomly from the Sambalpur locality. The treatment was assigned randomly, where the students of the experimental group were taught using metacognitive interventions i.e., thinking aloud, brainstorming, concept mapping, and self-assessment, and the students of the control group were taught by following the traditional approach. Achievement test in Education subjects was constructed and used.  The total number of 79 samples were taken into account (experimental group = 41, control group = 38) for experimentation. The collected data was analyzed with the help of Analysis of Covariance. The results of the study revealed a significant positive impact of metacognitive interventions on the academic achievement of higher secondary school students in Education with reference to contributors of educators, learning and motivation, and current issues in education. There was no significant interaction effect among strategy of teaching, gender, and caste on academic achievement of students in Education. The present study has implications for policymakers, principals, teachers, parents, and students.